Health Sciences: Advancing Healthcare through Interdisciplinary Approaches and Innovation - Sharma, Priya; Mishra, Ravinesh; Sharma, Bhartendu; Kumari, Archana; Modgil, Swati (Future Science / FSH-PH Publications, 2025)
Health sciences encompass a diverse range of disciplines that combine insights from medicine, biology, public health, nursing, pharmacology, and other related fields to enhance human health. The primary purpose is to improve the understanding of human health as it develops alongside disease progression together with treatment effectiveness for both personal and community populations. Healthcare systems now redirect their focus towards population health management while expanding medical care from conventional settings to community-based health strategies to deliver affordable quality services. Changes in the healthcare environment require professionals to master evidence-based methods while effectively using technology along with teamwork between different professionals. Healthcare has undergone revolutionary changes through medical research which has delivered breakthrough treatments through